Pneumonostomy in the Surgical Management of Hydatid Cyst of the Lung - Jehangir, Susan; Kurian, Jujju Jacob; Jacob, Tarun John; Gurram, Grace Mary; Thomas, Reju Joseph; Mathai, John; Karl, Sampath (European Journal of Pediatric Surgery, 2017)
Background Pneumonostomy in the surgical treatment of bilateral hydatid cyst of the lung(HCL) was described by Anand et al. This study presents the comparative long-term results of pneumonostomy for simple and complicated HCL.Methods and Patients The pneumonostomy technique was applied to both open and minimally invasive operations. The cyst was opened, endocyst removed, and any bronchial openings closed. The pericyst was closed over a 20-French Malecot tube, which was exteriorized and connected to an underwater seal. The tube was removed after 3 weeks by which time a well-established tract had formed. Hospital records of 26 children with 30 HCL who underwent pneumonostomy between 2001 and 2014 were reviewed and followed up. Patients were analyzed in two groups:group1 comprised uncomplicated and group2 complicated HCL. There was a statistically significant difference in the age at presentation in the two groups. The groups were comparable with respect to presenting symptoms, sex ratio, and side or size of cyst.Results Six(20%) children with surgical complications were graded by Clavien–Dindo classification. Three(10%) children qualified as grade 1 and did not require pharmacologic or surgical therapy. Three(10%) children had grade 3 complications; two developed empyema and one pneumothorax. There were no prolonged air leaks. Children with complicated cysts did not require longer hospitalization. Follow-up was possible in 80.76% of the children. The mean duration of follow-up was 21.3 months (interquartile range, 5–63 months). There were no postoperative recurrences or disease-related mortality.Conclusion Pneumonostomy is a safe and effective technique for dealing with the residual cavity in large complicated cysts and bilateral HCL.
Keywords: hydatid cyst of the lung; pulmonary hydatidosis; pneumonostomy